2016
DOI: 10.1186/s40478-016-0346-z
|View full text |Cite
|
Sign up to set email alerts
|

The retina as an early biomarker of neurodegeneration in a rotenone-induced model of Parkinson’s disease: evidence for a neuroprotective effect of rosiglitazone in the eye and brain

Abstract: Parkinson’s Disease (PD) is the second most common neurodegenerative disease worldwide, affecting 1 % of the population over 65 years of age. Dopaminergic cell death in the substantia nigra and accumulation of Lewy bodies are the defining neuropathological hallmarks of the disease. Neuronal death and dysfunction have been reported in other central nervous system regions, including the retina. Symptoms of PD typically manifest only when more than 70 % of dopaminergic cells are lost, and the definitive diagnosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
81
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(84 citation statements)
references
References 83 publications
1
81
0
2
Order By: Relevance
“…Cav-1 expression is induced by thiazolidinediones such as rosiglitazone, a PPAR γ agonist used to treat type 2 diabetes (Llaverias et al, 2004; Tencer et al, 2008). In the retina, these compounds suppress retinal and choroidal neovascularization (Higuchi et al, 2010; Murata et al, 2001; Murata et al, 2000), reduce diabetes-induced retinal vascular inflammation and BRB breakdown (Muranaka et al, 2006), and promote neuroprotection (Doonan et al, 2009; Li et al, 2011; Normando et al, 2016). It remains to be determined whether these effects are mediated through Cav-1 expression in the retina.…”
Section: Discussionmentioning
confidence: 99%
“…Cav-1 expression is induced by thiazolidinediones such as rosiglitazone, a PPAR γ agonist used to treat type 2 diabetes (Llaverias et al, 2004; Tencer et al, 2008). In the retina, these compounds suppress retinal and choroidal neovascularization (Higuchi et al, 2010; Murata et al, 2001; Murata et al, 2000), reduce diabetes-induced retinal vascular inflammation and BRB breakdown (Muranaka et al, 2006), and promote neuroprotection (Doonan et al, 2009; Li et al, 2011; Normando et al, 2016). It remains to be determined whether these effects are mediated through Cav-1 expression in the retina.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, the in vivo silencing of CAV1 by siRNA in the retina can suppress neovascularization and pathological BRB breakdown in ischemia-induced retinal disease [216]. It is noteworthy to mention that thiazolidinediones or peroxisome proliferator-activated receptorgamma (PPARγ) agonists that are used to treat T2DM, can suppress retinal neovascularization, attenuate retinal vascular inflammation and BRB breakdown, and promote neuroprotection in the retina [217,218]. PPARγ activation induces CAV1 [219] and has all the hallmarks of CAV1 action such as the previously mentioned decrease of insulin resistance, adipocyte regulation, and antiproliferative action [220].…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Parkinson's disease is a progressive neurodegenerative disorder characterised by loss of nerve cells in the substantia nigra of the brain and accumulation of Lewy bodies (abnormal aggregates of the protein, α‐synuclein) . This in turn results in loss of dopaminergic cells followed by a reduction in the neurotransmitter, dopamine.…”
Section: Parkinson's Diseasementioning
confidence: 99%
“…An OCT study in rotenone‐induced rodent models revealed retinal ganglion cell death and a temporary swelling of the retina after 20 days of rotenone insult; however, loss of dopaminergic cells was evident in the substantia nigra only after two months, suggesting that retinal changes may precede cell loss in the brain …”
Section: Parkinson's Diseasementioning
confidence: 99%